2023
DOI: 10.1111/cns.14338
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐brain monosynaptic inputs to lateral periaqueductal gray glutamatergic neurons in mice

Abstract: ObjectiveThe lateral periaqueductal gray (LPAG), which mainly contains glutamatergic neurons, plays an important role in social responses, pain, and offensive and defensive behaviors. Currently, the whole‐brain monosynaptic inputs to LPAG glutamatergic neurons are unknown. This study aims to explore the structural framework of the underlying neural mechanisms of LPAG glutamatergic neurons.MethodsThis study used retrograde tracing systems based on the rabies virus, Cre‐LoxP technology, and immunofluorescence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Because of its extensive connections with the cortex and various brainstem nuclei, PAG serves as a critical midbrain hub for sensory-motor integration (see Figure 1 for details; Zare et al, 2019 ; Schottelkotte and Crone, 2022 ; Ma et al, 2023 ). It primarily receives input from regions such as the medial prefrontal cortex (mPFC), central amygdala (CeA), anterior cingulate cortices (ACC), bed nucleus of the stria terminalis (BST), hypothalamus, and dorsal premammillary nucleus (PMD), allowing for the relay and integration of sensory information from diverse modalities ( Benarroch, 2012 ; Faull et al, 2019 ; Zare et al, 2019 ; Schottelkotte and Crone, 2022 ).…”
Section: Anatomical Structure and Neural Connections Of Pagmentioning
confidence: 99%
“…Because of its extensive connections with the cortex and various brainstem nuclei, PAG serves as a critical midbrain hub for sensory-motor integration (see Figure 1 for details; Zare et al, 2019 ; Schottelkotte and Crone, 2022 ; Ma et al, 2023 ). It primarily receives input from regions such as the medial prefrontal cortex (mPFC), central amygdala (CeA), anterior cingulate cortices (ACC), bed nucleus of the stria terminalis (BST), hypothalamus, and dorsal premammillary nucleus (PMD), allowing for the relay and integration of sensory information from diverse modalities ( Benarroch, 2012 ; Faull et al, 2019 ; Zare et al, 2019 ; Schottelkotte and Crone, 2022 ).…”
Section: Anatomical Structure and Neural Connections Of Pagmentioning
confidence: 99%
“…In the United States, individuals with this condition face an average potential loss of 28.5 years of life (3)(4)(5)(6). Pharmacological and brain imaging studies have demonstrated that disruptions in dopamine neurotransmission can result in psychiatric symptoms, such as delusions and hallucinations, whereas aberrant glutamate signaling may contribute to negative and cognitive symptoms (7)(8)(9). Nonetheless, there is an indication that various brain regions and circuits are extensively implicated, leading to a range of effects.…”
Section: Introductionmentioning
confidence: 99%